Recent advances of SNHG in regulating mesenchymal stem cell osteogenic differentiation - HUANG Jie; WANG Zuolin (Kouqiang hemian waike zazhi)
Bone healing and bore regeneration are complex processes in maintaining normal bone homeostasis. Mesenchymal stem cells are main resource of osteoblasts that are responsible for bone formation. Long noncoding RNA (lncRNA) is emerging as important regulatory role in the osteogenic differentiation of mesenchymal stem cells, in which lncRNA small nucleolar RNA host gene (SNHG) has been shown to be participated in mesenchymal stem cell osteogenic differentiation via various mechanisms, promising to be a new therapeutic target in bone metabolism and bone regeneration therapy. Herein, this article aims to review the biological functions and emerging mechanisms of SNHG involved in the mesenchymal stem cell osteogenic differentiation.